Comparison of endoscopic thyroidectomy by complete areola approach and conventional open surgery in the treatment of differentiated thyroid carcinoma: A retrospective study and meta-analysis - Yuan, Yuquan; Sun, Chenyu; Yin, Tingjie; Shao, Cong; Pan, Bin; Lu, Dengwei; Hou, Shaodong; Lowe, Scott; Bentley, Rachel; Chen, Shuya; Huang, Christy; Cheng, Ce; et al. (Frontiers in Surgery, 2022)
Background: The feasibility of endoscopic thyroidectomy by complete areola approach (ETCA) remains controversial. This study was conducted by combining our clinical data with the data obtained from a systematic review literature search to examine the effectiveness and safety of ETCA compared with conventional open thyroidectomy (COT) in differentiated thyroid carcinoma (DTC). Methods: A total of 136 patients with a diagnosis of DTC who underwent unilateral thyroidectomy with central neck dissection from August 2020 to June 2021 were enrolled. The enrolled patients were divided into the ETCA group(n=73) and the COT group(n=63). The operative time, intraoperative bleeding volume, number of removed lymph nodes, number of metastatic lymph nodes, postoperative drainage volume, length of postoperative hospital stay, postoperative parathyroid hormone (PTH) levels, and complications were analyzed. Then, a systemic review and comprehensive literature search were conducted by using PubMed, Google Scholar, Embase, Web of Science, CNKI, Wanfang, and VIP database up to June 2022. Review Manager software version 5.3 was used for the meta-analysis. Results: The results of clinical data showed that there were significant differences between the two groups in the operative time, intraoperative bleeding volume, removed lymph nodes, and postoperative drainage volume. There were no statistical differences in the length of postoperative hospital stay, number of metastatic lymph nodes, postoperative PTH level, and complications. In the systematic review and meta-analysis, 2153 patients from fourteen studies (including our data) were ultimately included. The results of the meta-analysis found that ETCA had a longer operative time, larger postoperative drainage volume, and lower intraoperative bleeding volume. In terms of the length of postoperative hospital stay, the number of removed lymph nodes, and surgical complications, there was no significant difference between the two groups. Conclusion: ETCA poses lower surgical bleeding and better cosmetic appearance compared with COT, while the length of operation and postoperative drainage in ETCA is less favorable compared with COT. In addition, ETCA is not inferior to COT in terms of postoperative hospitalization stay, the number of removed lymph nodes, and surgical complications. Given its overall advantages and risks, ETCA is an effective and safe alternative for patients with cosmetic concerns.